ANALISA KEBIJAKAN KOMISI PEMBERANTASAN KORUPSI TERKAIT TES WAWASAN KEBANGSAAN DALAM RANGKA PERALIHAN STATUS KEPEGAWAIAN KPK MENJADI APARATUR SIPIL NEGARA - Michael Marlee (Fakultas Hukum Universitas Tarumanagara, 2021)
“Tes Wawasan Kebangsaan” or often referred to as TWK has attracted a lot of polemics in the community as an effort to weaken the KPK which resulted in as many as 57 KPK employees being dismissed. This problem stems from year 2021 KPK regulations Number 1354 which determine that as a condition for transitioning KPK employee status to that of civil servant (ASN), they must get a passing degree for TWK. TWK is accused as a way to weaken the performance of KPK, does not have a clear legal basis and contradicts UUD NRI 1945. This study aims to examine the legal basis of TWK for the sake of legal certainty for the Indonesian people and see how TWK influences the performance of KPK. The research was conducted using normative research with legal materials related to laws and regulations, journals and website info as non-legal materials. Research shows that TWK has a clear legal basis because it is in accordance with existing laws and regulations. However, the dismissal of 57 KPK employees is an inappropriate KPK policy because it will create job vacancies and thus affect the performance of the KPK. For the sake of KPK in eradicating corruption, KPK should try to develop those 57 KPK employees who have competence and experience, instead of simply dismissing them.